Role of Intrastromal Bevacizumab in Reducing Corneal Neovascularization in Patients Presenting to a Tertiary Care Hospital in Multan - Ali, Kashif; Niazi, Muhammad Khizer; Malik, Saad Mushtaq; Riaz, Mehmood; Javeed, Danish; Waqas, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the effect of a single dose of intrastromal Bevacizumab on anomalous corneal neovessels in patients with corneal neovascularization. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital Multan, Pakistan from Apr to Sep 2022. Methodology: After taking informed consent, up to 0.1ml intrastromal injection of Bevacizumab (25mg/ml) was given to 50 eyes with Grade 3 or Grade 4 corneal neovascularization (The primary outcome measure was to assess the efficacy of a single dose of intrastromal Bevacizumab by assessing the decrease in the area of corneal neovascularization at the end of 6 weeks. Results: At the end of 6 weeks, regression and downgrading of corneal neovascularization were seen. Of the 23 eyes with Grade 4 corneal neovascularization, 21(91.3%) eyes were downgraded to Grade 3, and two eyes (8.69%) were downgraded to Grade 2. Of the 27 eyes with Grade 3 corneal neovascularization, 25 were downgraded to Grade 2(92.6%), and two were downgraded to Grade 1(7.4%). There was a significant decrease in the area of corneal neovascularization from 2.88±0.50 mm before injection and 1.83±0.54 mm after Bevacizumab (p=0.001). Conclusion: Intrastromal administration of a single dose of Bevacizumab reduced the invasion area of corneal neovascularization at the end of six weeks. The degree of reduction of neovascularization was also dependent on the Grade of corneal neovascularization. Intrastromal Bevacizumab is an effective treatment for corneal neovascularization with minimum local and systemic side effects.